Konsep Pembelajaran Berbasis Multiple Intelligences dalam Perspektif Munif Chatib - hasanah, uswatun (Tarbawiyah Jurnal Ilmiah Pendidikan, 2015)
Concept-Based Learning Multiple Intelligences Perspective Munif Chatib. Multiple intelligences-based learning in perspective Munif Chatib, occurs when a misunderstanding between the definition of multiple intelligences of educators with areal understanding of multiple intelligences. Munif Chatib explained that multiple intelligences is not really a field of study, nor is the curriculum. Of the existing context, several educational institutions, almost the majority of education in today’s schools are less likely to appreciate the full potential of the learners. Based learning multiple intelligences present as a realm of learning that focuses on the uniqueness and the uniqueness of each child always found excess. Departing from the above background, the researchers wanted to find out: how is the concept of multiple intelligences-based learning in perspective Munif Chatib. Multiple intelligences is acorrection to the concept of a person based on Intelligences intelligence quotient (IQ), which only measures a person’s ability based only on linguistic, logical mathematical and spatial only. Meanwhile, according to Howard Gardner man has multiple capabilities.The design concept of the application of Multiple Intelligences- based learning in schools globally covering three important stages, namely: input, process and output. At the input stage, using the Multiple Intelligences Research (MIR) in the acceptance of new students. The second stage is the stage of the learning process, which will have the same teacher teaching style to the learning style of learners. On output, the multiple intelligences-based learning, then the assessment is by using Authentic assessment. Authentic assessment is an assessment of the full figure of a learner who is not only measured in terms of the cognitive but also measured in terms of affective and psychomotor learners.